POSSIBILITIES OF DIFFERENT APPROACHES USING DURING DENTAL RESTORATION IN PRESCHOOL CHILDREN - J.I. Soloshenko (Український стоматологічний альманах)
Caries of temporary teeth in children occurs already from the first year of life, and the prevalence and intensity of early childhood caries tend to increase with age. Therefore, its treatment in children of early childhood and preschool age is a difficult but very important task for a dentist. The purpose of our study was to compare different approaches to oral hygiene in children of early childhood and preschool age. We examined 25 children aged 2 to 6 years who had suband decompensated caries and belonged to 2 health groups. These children were divided into two groups depending on the approach to dental treatment. The first group consisted of 10 children who were treated in outpatient settings. The second group consisted of 15 children who underwent oral rehabilitation under general anesthesia. The children of the first group were 5-6 years old persons, the second group included 2-5 years old children. Treatment of children of the 1st group, who had a positive attitude to dental manipulations, was carried out under local anesthesia in an outpatient setting. In the 2nd group of children who had either a negative attitude to dental treatment or an early age, rehabilitation was carried out under general anesthesia. Isolation of the working field was carried out using a rubberdam system. Universal nano-ceramic material SeramX SphereTEC one (Dentsply) was used for permanent fillings. When diagnosing pulpitis, treatment was carried out by the method of vital amputation or extirpation. Bio MTA Plus (Cerkamed P.P.H, Poland) was used as biological material during amputation, and Metapex filling material (Meta Biomed) was used to fill root canals during extirpation. Riva LC (SDI Limited, Australia) was used as a gasket for pulpitis.